DEVELOPMENT OF INTEGRATED SCIENCE STUDENT WORKSHEETS BASED ON A CONTEXTUAL APPROACH ON GLOBAL WARMING MATERIALS FOR CLASS VII SMP DEVELOPMENT OF INTEGRATED SCIENCE STUDENT WORKSHEETS BASED ON A CONTEXTUAL APPROACH ON GLOBAL WARMING MATERIALS FOR CLASS - cendikia aminah busrayuza; Skunda Diliarosta (Department of Science Education, 2022)
This research is based on integrated natural science worksheets which are not available in junior high school 1 Pariaman as well as the students' weak ability to associate the concept of learning material with the everyday environment. Efforts are being made to develop teaching materials in the form of worksheets with a contextual approach that can improve students' abilities in linking natural science learning that is integrated with the environment, especially global warming material. The type of research used is research development or Research and Development (R&D) with a 4-D model only carried out until the development stage. The validity test of the content feasibility component was obtained at 87.5% with the very valid category, the language component obtained an average validation value of 85% with the very valid category. Then in the presentation component obtained an average value of 82.22% with a very valid category and in the graphic component obtained an average value of 88% with a very valid category. The results of the study obtained an average validity score of 85.68% with a very valid category. So it can be concluded that the worksheets developed have met the criteria and are suitable for use in class VII natural science learning by teachers and students.